Scattering from an ionized column in the Earth-ionosphere space. - Wait, J.R.
An extension of an earlier paper (see ibid., vol.39, p.1051-4, July 1991) on this subject is hereby developed to allow for the generalization of the Born approximation to account for eddy currents in the column. Also, the relevance to VLF sprites is pointed out; these are ionized columns extending from the cloud tops to the low ionosphere
Keywords: Born approximation; Earth-ionosphere waveguide; VLF sprites; Cloud tops; Eddy currents; Electromagnetic scattering; Ionized column; Low ionosphere